Cytochrome c-cardiolipin complex in a nonpolar environment - Vikulina, A. S.; Alekseev, A. V.; Proskurnina, E. V.; Vladimirov, Yu. A. (Biochemistry-Moscow, 2015)
Programmed cell death (apoptosis) plays an important role in the life of multicellular organisms and in the development of socially significant human diseases. Cytochrome c-cardiolipin complex (Cyt-CL) is formed at the very beginning of a cascade of apoptotic reactions. Nevertheless, the structure of the complex and the mechanism of its participation in lipid peroxidation in mitochondrial membranes are not yet understood. In previous work (Vladimirov, Y. A., et al. (2011) Crystallography, 56, 712-719), it was shown that the Cyt-CL complex precipitates in concentrated water solution, the sediment containing orderly nanospheres formed by cytochrome c molecules with changed conformation and surrounded by a cardiolipin monolayer, and they are essentially hydrophobic. In this work, we obtained chloroform and hexane solutions of Cyt-CL with lipid/protein ratio of 77 ± 11. The conditions are described under which the solutions were obtained. Study of the properties of Cyt-CL solutions in hydrophobic media will reveal their structure and the mechanism of their catalytic activity inside the lipid layer of biological membranes.
CRIS-Team Scopus Importer:2021-06-08
Keywords: apoptosis; cardiolipin; cytochrome c; hydrophobic environment; lipid peroxidation